From systematic semiotic modelling to pseudointentional reference - Randviir, Anti (Sign systems studies, 2019)
Societies as open social systems work through semiotic modelling systems. We view their relevance for shaping primary and secondary needs, as well as metaneeds that are conditioned in social systems. Through conditioning in socialization, semiotic reality can be naturalized up to a level where we can start speaking about not only unconscious, but also unintentional semiosic activity. By that, the very realm of indexicality will be questioned. If indexicality is conjoined with unintended referentiality, then unintentional semiosis means the blurring and fusion of realities far beyond the so-called simulacral semiotic spaces. It is especially acute in the context of the development of technological availabilities where the physical, the semiotic, and the purely virtual reality merge. That quite novel phenomenon is exemplified by semiotic insularization. What follows is that it is hard to define the research object, for the subject is fading away, the real and the virtual are intermingling also in terms of their inhabitants (biological humans, computer users, avatars, virtual identities). Thus the pragmatic dimension of semiotics is gradually becoming lost. Also, the referential reality is moving farther from the informational space created and represented in “traditional” discursive flows, rather becoming based on pseudoreferential clues of meaning making.